Il était une fois... la formation à distance - Glikman, Viviane (Médiations et médiatisations, 2021)
This editorial presents different views to approach the history of distance learning. If the history of technologies is the most frequently explored, this paper also presents the history of pedagogies and the various contexts surrounding devices and their evolution, specialized institutions in the field and the terminologies used to name different actions. Subsequently, it presents the papers of the current issue that adopted some of these views on the topic.
Keywords: contexte sociétal; formation en ligne; formation à distance; histoire; institutions; pédagogie; technologies